PELAKSANAAN TOTAL QUALITY MANAGEMENT (TQM) DALAM LAYANAN KANTOR - Mareta, Evi; Arwan, Arwan; Marlina, Leny; Atika, Nyimas (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to analyse the implementation of Total Quality Management (TQM) in improving public service quality at the Ilir Barat II Sub-District Office in Palembang, with a particular focus on employee education and training as strategic elements in continuous improvement. This study uses a qualitative descriptive approach through observation, interviews, and documentation. The results of the study indicate that the basic principles of TQM, such as customer orientation, employee involvement, and continuous improvement, have begun to be implemented, but still face challenges in terms of limited human resources, digital infrastructure, and the lack of optimal routine employee training. The novelty of this study lies in the finding that the implementation of TQM will not be effective without the integration of continuous education and training designed based on employee competency needs. This study proposes a model for strengthening the capacity of civil servants based on needs-based training and digital literacy to bridge the generational gap among employees in digital services. Thus, this study not only expands the perspective on the application of TQM at the sub-district level but also provides practical contributions to the development of employee training policies within the framework of quality-based bureaucratic reform.